EARLY OUTCOMES OF INTERLAMINAR ENDOSCOPIC DISCECTOMY FOR SINGLE-LEVEL LUMBAR DISC HERNIATION AT THAI NGUYEN NATIONAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Introduction: Lumbar disc herniation is a condition characterized by the localized displacement of the nucleus pulposus beyond its normal boundaries, compressing the spinal canal or nerve roots, leading to pain, weakness, or numbness along the distribution of the affected nerve root. This condition significantly impacts patients’ quality of life and work capacity [1]. At the Department of Neurosurgery – Spine, Thai Nguyen National Hospital, interlaminar endoscopic discectomy has been commonly and routinely applied in the treatment of lumbar disc herniation.Objective: To evaluate the early outcomes of interlaminar endoscopic discectomy for the treatment of single-level lumbar disc herniation at Thai Nguyen National Hospital.Subjects and Methods: A cross-sectional descriptive study was conducted on 48 patients diagnosed with single-level lumbar disc herniation, who underwent endoscopic lumbar discectomy at the Department of Neurosurgery – Spine, Thai Nguyen National Hospital, from January 2022 to June 2025.Results: Among 48 cases of single-level lumbar disc herniation treated with interlaminar endoscopic discectomy, there were 28 males and 20 females. The mean age of the study group was 48.6 ± 11.80 years. Postoperative leg pain and back pain scores improved significantly, with mean reductions of 4.73 and 2.79 points, respectively. The mean postoperative ODI score was 17.51%, compared to 58.98% preoperatively. Good and excellent outcomes after surgery accounted for 91.8%, while fair outcomes accounted for 8.1%.Conclusion: Interlaminar endoscopic discectomy for the treatment of single-level lumbar disc herniation yields excellent early outcomes. This procedure should be maintained and widely applied.
Keywords: Percutaneous endoscopic lumbar discectomy, interlaminar approach, disc herniation.